Siccanin Is a Dual-Target Inhibitor of Plasmodium falciparum Mitochondrial Complex II and Complex III - Keisuke Komatsuya; Takaya Sakura; Kazuro Shiomi; Satoshi Ōmura; Kenji Hikosaka; Tomoyoshi Nozaki; Kiyoshi Kita; Daniel Ken Inaoka (MDPI AG, 2022)
Plasmodium falciparum contains several mitochondrial electron transport chain (ETC) dehydrogenases shuttling electrons from the respective substrates to the ubiquinone pool, from which electrons are consecutively transferred to complex III, complex IV, and finally to the molecular oxygen. The antimalarial drug atovaquone inhibits complex III and validates this parasite's ETC as an attractive target for chemotherapy. Among the ETC dehydrogenases from P. falciparum, dihydroorotate dehydrogenase, an essential enzyme used in de novo pyrimidine biosynthesis, and complex III are the two enzymes that have been characterized and validated as drug targets in the blood-stage parasite, while complex II has been shown to be essential for parasite survival in the mosquito stage; therefore, these enzymes and complex II are considered candidate drug targets for blocking parasite transmission. In this study, we identified siccanin as the first (to our knowledge) nanomolar inhibitor of the P. falciparum complex II. Moreover, we demonstrated that siccanin also inhibits complex III in the low-micromolar range. Siccanin did not inhibit the corresponding complexes from mammalian mitochondria even at high concentrations. Siccanin inhibited the growth of P. falciparum with IC50 of 8.4 μM. However, the growth inhibition of the P. falciparum blood stage did not correlate with ETC inhibition, as demonstrated by lack of resistance to siccanin in the yDHODH-3D7 (EC50 = 10.26 μM) and Dd2-ELQ300 strains (EC50 = 18.70 μM), suggesting a third mechanism of action that is unrelated to mitochondrial ETC inhibition. Hence, siccanin has at least a dual mechanism of action, being the first potent and selective inhibitor of P. falciparum complexes II and III over mammalian enzymes and so is a potential candidate for the development of a new class of antimalarial drugs.